2021
DOI: 10.25299/jgeet.2021.6.4.6242
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity Method for Characterising Subsurface Layers of Coastal Areas In South Sulawesi, Indonesia

Abstract: The data presented in this paper are related to the characterization of a subsurface layer of coastal area in South Sulawesi. This research will fill the gap in the resistivity method study which is this method not yet use in the coastlines area, especially area influenced by seawater and coastal condition impact like South Sulawesi. The method used in this study is the method of resistivity Wenner configuration by taking the data 1-2 lines each region with lengths 45 m, 75 m, 105 m, and 120 m respectively. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The lowest layer is the rock layer with the highest resistivity value of 100.1 Ωm -> 274 Ωm. The resistivity value can be interpreted as a layer of limestone (Azis et al, 2023;Rahmaniah et al, 2021). Located at 74 -112 meters with a depth of 12.5 -31.9 meters.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest layer is the rock layer with the highest resistivity value of 100.1 Ωm -> 274 Ωm. The resistivity value can be interpreted as a layer of limestone (Azis et al, 2023;Rahmaniah et al, 2021). Located at 74 -112 meters with a depth of 12.5 -31.9 meters.…”
Section: Resultsmentioning
confidence: 99%
“…Both studies successfully identified the presence of freshwater. In South Sulawesi, similar research was conducted by Rahmaniah et al (2021), but this research is considered too regional so it needs to be done more locally, especially in the Soreang Village area, Maros Regency.…”
Section: Introductionmentioning
confidence: 99%